Gaia DR3 data consistent with a short bar connected to a spiral arm - Vislosky, Ethan; Minchev, I; Khoperskov, S; Martig, M; Buck, Tobias; Hilmi, T; Ratcliffe, B; Bland-Hawthorn, J; Quillen, A C; Steinmetz, M; de Jong, R (Monthly notices of the Royal Astronomical Society, 2024)
We use numerical simulations to model Gaia  DR3 data with the aim of constraining the Milky Way (MW) bar and spiral structure parameters. We show that both the morphology and the velocity field in MW-like galactic disc models are strong functions of time, changing dramatically over a few tens of Myr. This suggests that by finding a good match to the observed radial velocity field, vR(x, y), we can constrain the bar-spiral orientation. Incorporating uncertainties into our models is necessary to match the data; most importantly, a heliocentric distance uncertainty above 10-15 per cent distorts the bar’s shape and vR quadrupole pattern morphology, and decreases its apparent angle with respect to the Sun-Galactocentric line. An excellent match to the Gaia  DR3 vR(x, y) field is found for a simulation with a bar length Rb ≈ 3.6 kpc. We argue that the data are consistent with an MW bar as short as ∼3 kpc, for moderate strength inner disc spiral structure (A2/A0 ≈ 0.25) or, alternatively, with a bar length up to ∼5.2 kpc, provided that spiral arms are quite weak (A2/A0 ≈ 0.1), and is most likely in the process of disconnecting from a spiral arm. We demonstrate that the bar angle and distance uncertainty can similarly affect the match between our models and the data - a smaller bar angle (20° instead of 30°) requires smaller distance uncertainty (20 per cent instead of 30 per cent) to explain the observations. Fourier components of the face-on density distribution of our models suggest that the MW does not have strong m = 1 and/or m = 3 spirals near the solar radius.
Veröffentlicht: 12. Februar 2024
Gesehen am 30.07.2024